Creep Behaviour under SiCp Exponential Volume Reinforcement in FGM Composite Rotating Cylinders. (2017) - Sahni, Manoj; Sahni, Ritu; Mehta, Parth
Abstract: In this paper we consider the problem of a rotating composite cylinder and study the secondary creep behaviour under SiCp exponential volume reinforcement. The use of rotating cylinders are diversified such as in generating lift in UAV, rotor ship, rotary piston engine, etc. Here, Norton's creep law is considered for the study of secondary creep behaviour. The effect of internal pressure on a rotating composite cylinder is also studied. Radial and circumferential stresses and strains are obtained for a cylinder with and without rotation. It is observed that with the increase in internal pressure, both the stresses show a sharp increase. With the exponential reinforcement of SiCp, the circumferential stress changes which act as a resisting force as compared to the radial stress. The change in the tangential stress depends on the gradation index of the exponential parameter. Results for radial and tangential stresses and strains are analytically obtained and the graphs are drawn for different parameters. The results obtained are also compared with those of non - FGM cylinders.